Identificación de posibles beneficios indebidos en los programas sociales y de actos de nepotismo en el estado - Quispe Huaman, Sergio Augusto (2023)
Peru in recent years has had sustained economic growth, together with population growth, the need for the government to provide more and better services to citizens was generated. However, the growth of the government has been disorderly and instead of adapting to technological advances it has suffered a stagnation that has given way to a disorganized government lacking instruments that simplify its processes. Consequently, this lack of organizational virtues has been a propitious space for corruption in its different forms. In addition to this, the control activities in public entities have a coverage gap, both in aspects of process control and of people, which would allow the identification of functional misconduct or acts of corruption committed by officials or public servants on a larger scale. Attention to this problem is very important for the actors of institutional control and the creation of public value, due to the fact that in recent years a very high economic loss has been generated for the government, which has a negative impact on the well-being of citizens. In this sense, the present work intends to generate a proposal to improve institutional control through the use of new technologies that allow the identification of possible undue beneficiaries in social programs and possible acts of nepotism in public entities, having as input various government data sources.